Missionary interventions in Zulu religious practices: the term for the Supreme Being - M. R. Masubelele (Acta Theologica)
The traditional Zulu people conducted their religious practices orally and in their appeals to a Supreme Being used the terms uNkulunkulu (the Great-Great-One) or uMvelinqangi (the First-to-Appear) interchangeably. However, with the translation of the Bible into isiZulu, the concept of the Supreme Being that was originally known by the Zulu people was changed and cast into a Christian mould. This paper explains these interventions in terms of Toury’s work. By using a corpus-based approach, the linguistic choices of the translators will be analysed to demonstrate that the earliest translators adopted the norms of the source text and culture, while in the latest translations the norms of the target culture were adhered to.